Preparation and Characterization of Nano Hybrid Antifungal from Amphotericin B and Evaluation its Inhibitory Efficiency against Candidaalbicans - Mays Ibrahim Al-Wakeel (Journal of Global Pharma Technology, 2018)
Direct ion exchange method was used to prepare a nanohybrid antifungal from Amphotericin B (AmB) and layered double hydroxides (LDH).The new nanoantifungal was subjected to identification .FT-IR spectroscopy revealed the appearance of new chemical groups in the prepared antifungal which indicates the formation of new compound. The X-Ray Diffraction (XRD) spectrum revealed the appearance of new diffraction planes in the nanohybrid antifungal in compare with the spectrum of layered double Hydroxides. The two and three dimensional image of the above compound obtained from atomic force microscope confirmed the formation of new antifungal with nanodimensions. The antifungal activity of prepared compound was evaluated against Candida albicans isolated from mouth and vagina.Keywords: Amphotericin B, Nanohybrid antifungal, FTIR, XRD, Controlled release, Antifungal activity